A literature survey on older adults' use of social network services and social applications. (May 2016) - Coelho, José; Duarte, Carlos
Abstract: With aging, adults which once worked and were active become isolated from the world because with retirement comes a whole range of problems which span from the physical to the social scope. One of the most concerning is social isolation, which can only be fought by satisfying social needs. In terms of technology, the challenges are in designing social technologies that encourage older people to actively engage with each other and with the people around them. This paper presents a survey reviewing research surrounding the emergent field of Social Network Services (SNSs), along with other meaningful social applications, and its use by the older segment of the population. A total of thirteen domains are identified related with how these services can be improved to consider older adults characteristics: from the most important related with the family role and privacy control, to issues related with the design of the user interface, the importance of multimodal interaction and adaptive solutions to compensate age-related declines, to several other focusing on the importance of groups, photos, cultural and health information. Main contributions to the field of SNS and older adults are given in a set of recommendations which result from discussions on each domain and which aim at the design of a more inclusive SNS solution. Highlights: We review literature surrounding Social Network Services and applications. Identified the 13 most relevant domains concerning older adults. Compiled a list of recommendations concerning the development of inclusive SNS. Family, interface complexity and privacy issues are the most important domains. Photos, multimodal interaction and adaptation play an important role on adoption.